Decarbonising the critical sectors of aviation, shipping, road freight and industry to limit warming to 1.5–2°C. (21st April 2021) - Sharmina, M.; Edelenbosch, O. Y.; Wilson, C.; Freeman, R.; Gernaat, D. E. H. J.; Gilbert, P.; Larkin, A.; Littleton, E. W.; Traut, M.; van Vuuren, D. P.; Vaughan, N. E.; Wood, F. R.; et al.
ABSTRACT: Limiting warming to well below 2°C requires rapid and complete decarbonisation of energy systems. We compare economy-wide modelling of 1.5°C and 2°C scenarios with sector-focused analyses of four critical sectors that are difficult to decarbonise: aviation, shipping, road freight transport, and industry. We develop and apply a novel framework to analyse and track mitigation progress in these sectors. We find that emission reductions in the 1.5°C and 2°C scenarios of the IMAGE model come from deep cuts in CO2 intensities and lower energy intensities, with minimal demand reductions in these sectors' activity. We identify a range of additional measures and policy levers that are not explicitly captured in modelled scenarios but could contribute significant emission reductions. These are demand reduction options, and include less air travel (aviation), reduced transportation of fossil fuels (shipping), more locally produced goods combined with high load factors (road freight), and a shift to a circular economy (industry). We discuss the challenges of reducing demand both for economy-wide modelling and for policy. Based on our sectoral analysis framework, we suggest modelling improvements and policy recommendations, calling on the relevant UN agencies to start tracking mitigation progress through monitoring key elements of the framework (CO2 intensity, energy efficiency, and demand for sectoral activity, as well as the underlying drivers), as a matter of urgency. Key policy insights Four critical sectors (aviation, shipping, road freight, and industry) cannot cut their CO2 emissions to zero rapidly with technological supply-side options alone. Without large-scale negative emissions, significant demand reductions for those sectors' activities are needed to meet the 1.5–2°C goal. Policy priorities include affordable alternatives to frequent air travel; smooth connectivity between low-carbon travel modes; speed reductions in shipping and reduced demand for transporting fossil fuels; distributed manufacturing and local storage; and tightening standards for material use and product longevity. The COVID-19 crisis presents a unique opportunity to enact lasting CO2 emissions reductions, through switching from frequent air travel to other transport modes and online interactions. Policies driving significant demand reductions for the critical sectors' activities would reduce reliance on carbon removal technologies that are unavailable at scale.